Go For Integrated Marketing Communication: Exploring the Impact and Implementation of Integrated Marketing Communication (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Integrated marketing communication (IMC) is being practiced worldwideat very large scale and it is one of the most controversial areas of research,the concept marking a constant progress from the simple coordinating ofpromotional tools to a complex strategic process. Further to the evolution ofmodern marketing, where IMC has become a major way of achievement theobjectives of a company, there is a need to identify opportunities to increaseits impact on consumer behaviour. The purpose of this review paper is toenhance the understanding of what is IMC, its impact and the difference betweenIMC and traditional marketing communication. Integrated marketing communicationis consumer oriented approach rather than organizational oriented that focuseson organizational needs. IMC is performed in a manner of synergy rather than inisolation. It is associated with some positive results like brand awareness,customer satisfaction, brand loyalty, positive brand image, unique brandassociation, greater profitability, increased sales and cost savings. IMC hasmajor impact on organizational performance and brand equity. There are somebarriers to successful implementation of IMC program.